Designing a Web-Based New Employee Recruitment Information System with the Waterfall Method at Nassa School - Aulia, Nida (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study aims to design a web-based employee recruitment information system for Nassa School Bekasi using the Waterfall method to address practical issues in recruitment processes. Utilizing a combination of observation, interviews, and literature studies, data were collected and analyzed to specify software needs, interface design, databases, and functional requirements. The system was developed using PHP, JavaScript, HTML, CSS, and Bootstrap with MySQL for the database. The resulting system simplifies the recruitment process, reduces administrative errors, and increases efficiency, offering practical guidance for similar implementations in other institutions.